A Study on the Alignment between Life Textbook Activities and Multiple Intelligence Profiles of College students: a perspective from multple intelligences theory - Phan Thị Hồng Việt (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study aims to analyze the activities in the Life (A1-A2 2nd Edition) textbook (Life textbook) relating to MIT in order to determine the level of multipleintelligences in this book and their alignment to MI profiles of college students. It is critical to analyze textbook activities and offer some alternate exercises that may strengthen students' strengths and improve their flaws. This will serve as the foundation for recommending activities supplementing the activities given in the textbook in order to assist students to learn successfully by developing their multiintelligence. Because each student has a unique learning style and strategy, learningactivities are developed to ensure that students with different intelligences maylearn successfully in class. The major goal is to increase the learning efficiency of students based on their multiple intelligences